Acta Universitatis Danubius. Œconomica, Vol. 14, No. 2 - part 1: Array - Collective Authors, (Acta Universitatis Danubius. Œconomica, 2021)
The study investigates the impact of oil price fluctuations on foreign direct investment inflows in developing oil exporting countries using Nigeria as a case study by ARDL method and VECM granger causality test to analyse the data spanning from 1970 to 2015. It was observed that oil price fluctuations do not favour foreign direct investment in Nigeria both in the long-run and shortrun. This implies that as oil price changes foreign direct investment inflows falls. VECM granger causality test revealed that there is no direction of causality between oil price fluctuations and foreign direct investment inflows in Nigeria. We therefore concluded that oil price is not an important determinant of foreign direct investment inflows. The study recommends that government should take the advantage of times of positive change in the oil price to fix the needs to attract foreign direct investment inflows in the economy.